Dr. Wilbur Hah — Deep Plane Facelift — Orange - Hah, Wilbur (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Wilbur Hah, practicing in Orange, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002964; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; orange